EAFF Advocacy newsletter - Voice of Farmers in Eastern Africa , April-September 2010 - East African Farmers Federation (Eastern Africa Farmers Federation (EAFF), 2010)
In this edition, EAFF provides a brief report of the meeting held between the EAFF board and two Members of Parliament from the East African Legislative Assembly and a summary on an investigation undertaken by EAFF on the policy-making process at the East African Community...